Thomas LEITCH, editor. The Oxford Handbook of Adaptation Studies. Oxford UP, 2017. ISBN: 9780199331000. 762 pp. - Cass, Richard (Anafora, 2023)
The Oxford Handbook of Adaptation Studies (2017) is a massive volume in more ways than one. Weighing over 2lbs (1.3 kg), it contains forty articles on various aspects of adaptation written by a catalogue of star names in the very ambitious attempt to cover all aspects of adaptation studies. Offering specific suggestions pertinent to all ways of scholarly interaction with adaptation, that is, how to adapt texts, and how to subsequently teach, read, and write about adaptation, The Oxford Handbook of Adaptation Studies, paradoxically, at the same time reveals the adaptation’s mutability and versatility, and wants to fix its every aspect. Moreover, rather than being ground-breaking in its entirety, much of it represents a summary of knowledge available so far in other publications.